Perlindungan Hukum Anak Korban Child Grooming melalui Media Sosial TikTok - Ainun Isti Khomah; Niluh Sridewi Rahayu; Fuad Nur (Jurnal Ilmu Sosial dan Humaniora, 2026)
The development of information and communication technology has shifted the pattern of sexual crimes against children from physical spaces to digital spaces. TikTok, as one of the social media platforms widely used by children and teenagers, has various interactive features that provide opportunities for perpetrators to approach children online through child grooming practices. This study aims to analyze legal protection for children as victims of child grooming crimes through the social media platform TikTok, as well as efforts to recover victims from a victimology perspective.  The result of this research, from a victimology perspective, emphasizes that protecting children in the digital space shouldn't stop at imprisoning the perpetrators. Instead, it should ensure full recovery efforts for the victims through three urgent measures: fulfilling the victims' right to material restitution from the perpetrators, ongoing psychological rehabilitation by the UPTD PPA/LPSK to address cyber trauma, and the right to quickly erase digital traces the right to be forgotten through TikTok in collaboration with the Ministry of Communication and Digital Affairs to break the chain of secondary victimization. Protection for victims of child grooming is also guaranteed by the state through Law Number 35 of 2014 on Child Protection, Law Number 1 of 2024 on Electronic Information and Transactions, Law Number 1 of 2023 on the Criminal Code, and Law Number 12 of 2022 on the Crime of Sexual Violence.